5.0k views
5 votes
help help help help help help help help help help help help help help help help help help help help help help help help help help help help help help help help ​

help help help help help help help help help help help help help help help help help-example-1

2 Answers

6 votes

Answer:

see explanation

Explanation:

using the following expansions

a² + 2ab + b² = (a + b)²

a² - 2ab + b² = (a - b)²

1

x² - 12x + 36

with a = x and b = 6 , then

x² - 12x + 36 = x² - 2(x)(6) + 6² = (x - 6)²

2

x² + 22x + 121

with a = x and b = 11 , then

x² + 22x + 121 = x² + 2(x)(11) + 11² = (x + 11)²

3

x² - 8xy + 16y²

with a = x and b = 4y , then

x² - 8xy + 16y² = x² - 2(x)(4y) + 16y² = (x - 4y)²

4

25x² - 10xy + y²

with a = 5x and b = y , then

25x² - 10xy + y² = 25x² - 2(5x)(y) + y² = (5x - y)²

User Magno
by
4.5k points
1 vote

Answer:

1. -10x+36

2. 24x+121

3. 2x-8xy+32y

4. 50x-10xy+y^2

Explanation:

i think dis right

User Puvanarajan
by
6.0k points